Naringin Attenuates High Fat Diet Induced Non-alcoholic Fatty Liver Disease and Gut Bacterial Dysbiosis in Mice - Mu, Hongna; Zhou, Qi; Yang, Ruiyue; Zeng, Jie; Li, Xianghui; Zhang, Ranran; Tang, Weiqing; Li, Hongxia; Wang, Siming; Shen, Tao; Huang, Xiuqing; Dou, Lin; et al. (Frontiers in Microbiology, 2020)
The incidence of non-alcoholic fatty liver disease (NAFLD) is rising annually, and emerging evidence suggests that the gut bacteria plays a causal role in NAFLD. Naringin, a natural flavanone enriched in citrus fruits, is reported to reduce hepatic lipid accumulation, but to date, no investigations have examined whether the benefits of naringin are associated with the gut bacteria. Thus, we investigated whether the antilipidemic effects of naringin are related to modulating the gut bacteria and metabolic functions. In this study, C57BL/6J mice were fed a high-fat diet (HFD) for 8 weeks, then fed an HFD with or without naringin administration for another 8 weeks. Naringin intervention reduced the body weight gain, liver lipid accumulation, and lipogenesis and attenuated plasma biochemical parameters in HFD-fed mice. Gut bacteria analysis showed that naringin significantly altered the community compositional structure of the gut bacteria characterized by increased benefits and fewer harmful bacteria. Additionally, Spearman’s correlation analysis showed that at the genus level, Allobaculum, Alloprevotella, Butyricicoccus, Lachnospiraceae_NK4A136_group, Parasutterella and uncultured_bacterium_f_Muribaculaceae were negatively correlated and Campylobacter, Coriobacteriaceae_UCG-002, Faecalibaculum and Fusobacterium were positively correlated with serum lipid levels. These results strongly suggest that naringin may be used as a potential agent to prevent gut dysbiosis and alleviate NAFLD.